The Role of AIESEC in Implementing SDGS No. 4 Through Global Volunteers in the Suphanburi, Thailand - Rahmad Eko Wiranto; Shannaz Mutiara Deniar; Bhornpat Pornsuratana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
This research examines the role of AIESEC as an international organization in facilitating the implementation of SDGs through Global Volunteers in Suphanburi, Thailand. The SDGs' implementation affects getting involved and contributing actively to making the world a better place, especially regarding "Quality of Education." As a forum for facilitating education, it is necessary to consider the need for space for international organizations to provide various roles. As one of the significant organizations, AIESEC plays a role in providing real action to youth by contributing to the development of globalization. The research method uses qualitative research through library research from several journals, news, and data from AIESEC in this research. The result shows that the implementation of SDGs through Global Volunteers realizes and facilitates the development of education, especially in Suphanburi, which is a challenge, but can develop and will continue to evaluate how to create a globally supportive role. Therefore, AIESEC facilitates global values, activities, and program initiatives to support by implementing SDGs no 4, which is in the form of direct teaching materials to educate children in schools and communities to improve the quality of education and broaden horizons globally from English Day Teaching, Community Service, and also Global Village.